2007 IEEE/SP 14th Workshop on Statistical Signal Processing 2007
DOI: 10.1109/ssp.2007.4301286
|View full text |Cite
|
Sign up to set email alerts
|

On sensing capacity of sensor networks for a class of linear observation models

Abstract: In this paper we address the problem of finding the sensing capacity of sensor networks for a class of linear observation models and a fixed SNR regime. Sensing capacity is defined as the maximum number October 27, 2018 DRAFT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…However, in many practical applications, obtaining some large fraction of these positions would be sufficient. Neither the limits of partial sparsity recovery nor the performance of practical algorithms are completely understood, though some results have been reported in [20]- [22], [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, in many practical applications, obtaining some large fraction of these positions would be sufficient. Neither the limits of partial sparsity recovery nor the performance of practical algorithms are completely understood, though some results have been reported in [20]- [22], [24].…”
Section: Discussionmentioning
confidence: 99%
“…For a strict sparse scene, we have 2 0 0 σ → , which means absence of clutter in a radar scene. We can simplify its rate distortion function [39]:…”
Section: Sparse Radar Scenes and Rate-distortion Characterizationmentioning
confidence: 99%
“…They drive the bounds on the sufficient number of measurements for distributed encoding exploiting CS theory. [10] also addressed the problem of finding sensing capacity of sensor networks that is defined as the maximum number of signal dimensions per sensor observation. It showed that sensing capacity decreases as sensing diversity per sensor decreases.…”
Section: B Compressive Sensing Based Wireless Sensor Networkmentioning
confidence: 99%